A Comparative Pharmacokinetic Study of Myrislignan by UHPLC–MS After Oral Administration of a Monomer and Myristica fragrans Extract to Rats - Zhu, Zhe (J Chromatogr Sci, 2016)
An ultra-high performance liquid chromatography coupled with mass spectrometry (UHPLC–MS) method was developed and validated to quantify myrislignan in rat plasma using podophyllotoxin as an internal standard (IS). The chromatographic separation of myrislignan and IS was performed on a 3.0 µm Hypersil C(18) column (50 mm × 4.6 mm) with methanol and water containing 0.1% acetic acid (80:20, v/v) as the mobile phase at a ﬂow rate of 0.3 mL/min. An electrospray ionization was used in the positive selective-ion monitoring mode for the target ions at m/z 397 and m/z 437 for the quantification of myrislignan and IS. The total run time was 3.6 min for each run. The calibration curve was linear over the range of 0.75–300 ng/mL (r > 0.995) with the lower limit of quantitation at 0.75 ng/mL. Intra- and interday precision was below 11.49%, and the mean accuracy ranged from −9.75 to 7.45%. The proposed method was successfully applied to evaluate the pharmacokinetic properties of myrislignan after oral administration of the myrislignan monomer and Myristica fragrans extract in rats. Statistical analyses indicate that the pharmacokinetic properties of myrislignan in rats have significant differences between two groups.